Communication Skills and Work Readiness of Senior High School Technical-Vocational-Livelihood Track Students - Yoshida, Yoshimitsu; Guzman, Rodel (Journal of Interdisciplinary Perspectives, 2025)
Effective communication is a critical competency for workplace success, particularly for Senior High School (SHS) students who are preparing for employment under the Technical-Vocational-Livelihood (TVL) track. This study examines the communication skills of SHS-TVL students and their relationship with work readiness, comparing students’ self-assessments with teachers’ evaluations. A descriptive- correlational research design was employed, involving 330 students and 108 teachers from various TVL strands. A structured questionnaire assessed communication skills across five domains—verbal, written, non-verbal, active listening, and problem-solving communication—alongside work readiness indicators such as work attitude, technical skills, social skills, and organizational awareness. Data were analyzed using descriptive statistics, paired t-tests, Pearson correlation, and multiple regression analysis. Findings indicate that students and teachers perceive communication skills as low, with teachers rating students significantly lower across all dimensions. The most notable gap was observed in non-verbal and written communication. A significant positive correlation was found between communication skills and work readiness (r = 0.50, p< 0.01), with non-verbal communication emerging as the strongest predictor of work readiness (β = 0.27, p< 0.001). These results underscore the need for structured communication training in the TVL curriculum, including role-playing exercises, workplace simulations, and industry partnerships to enhance real-world communication exposure. Future research should explore longitudinal assessments to track communication skill development beyond graduation. Strengthening students’ communication competencies is essential to bridging the gap between technical training and employability, ensuring that SHS-TVL graduates are well- prepared for professional environments.